Improvement of technical parameters of fire vehicles and equipment - Suslavičius, Vladimiras; Bogdevičius, Marijonas (Transport, 2003)
The improvement of the technical parameters of the fire vehicle implemented in a few groups is presented. Each parameter of these groups has a respective impact on the following features of the fire vehicle. The deficiencies of the main fire vehicles under operation, the improvement of the fire vehicles vacuum systems and extinguishing systems are presented.First Published Online: 19 Dec 2011